Editorial note. (16th December 2016) - MITKOV, RUSLAN
Abstract : In one of my previous editorial notes I promised that the positive developments of the Journal of Natural Language Engineering (JNLE) would be a continuous and common practice. I am proud to report that I have been able to keep this promise. JNLE has enjoyed another very successful year. The impact factor of the journal increased for the second consecutive year, with the journal listed both among the Linguistics and Computer Science categories. From 2016 onwards, JNLE is offering six 160-page issues per year, which by far exceeds the four 96-page issues from less than 10 years ago!